Aircraft control allocation - Durham, Wayne, 1941-; Bordignon, Kenneth A.; Beck, Roger, 1977- (John Wiley & Sons, Inc., 2016)
Aircraft Control Allocation Wayne Durham, Virginia Polytechnic Institute and State University, USA Kenneth A. Bordignon, Embry-Riddle aeronautical University, USA Roger Beck, Dynamic Concepts, Inc., USA An authoritative work on aircraft control allocation by its pioneers Aircraft Control Allocation addresses the problem of allocating supposed redundant flight controls. It provides introductory material on flight dynamics and control to provide the context, and then describes in detail the geometry of the problem. The book includes a large section on solution methods, including 'Banks' method', a previously unpublished procedure. Generalized inverses are also discussed at length. There is an introductory section on linear programming solutions, as well as an extensive and comprehensive appendix dedicated to linear programming formulations and solutions. Discrete-time, or frame-wise allocation, is presented, including rate-limiting, nonlinear data, and preferred solutions. Key features: -Written by pioneers in the field of control allocation.-Comprehensive explanation and discussion of the major control allocation solution methods.-Extensive treatment of linear programming solutions to control allocation.-A companion web site contains the code of a MATLAB/Simulink flight simulation with modules that incorporate all of the major solution methods.-Includes examples based on actual aircraft. The book is a vital reference for researchers and practitioners working in aircraft control, as well as graduate students in aerospace engineering.
Keywords: Airplanes -- Control systems -- Mathematics.; Airplanes -- Control systems -- Design and construction.; elektronické knihy; electronic books